2006
DOI: 10.1089/neu.2006.23.1379
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Bone Marrow Stem Cells as well as Mobilization by Granulocyte-Colony Stimulating Factor Promotes Recovery after Spinal Cord Injury in Rats

Abstract: Emerging clinical studies of treating brain and spinal cord injury (SCI) with autologous adult stem cells led us to compare the effect of an intravenous injection of mesenchymal stem cells (MSCs), an injection of a freshly prepared mononuclear fraction of bone marrow cells (BMCs) or bone marrow cell mobilization induced by granulocyte colony stimulating factor (G-CSF) in rats with a balloon- induced spinal cord compression lesion. MSCs were isolated from rat bone marrow by their adherence to plastic, labeled w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
135
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(142 citation statements)
references
References 53 publications
3
135
1
3
Order By: Relevance
“…MSCs can be mobilized from the marrow or can be expanded in culture and delivered to the damaged site by direct or systemic injection. 22 Once at the site of injury, MSCs produce factors that inhibit scarring and apoptosis, promote angiogenesis and stimulate host progenitors to divide and differentiate in order to repair the injured tissue. In this regard, the trophic effects of MSCs may have important clinical use.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…MSCs can be mobilized from the marrow or can be expanded in culture and delivered to the damaged site by direct or systemic injection. 22 Once at the site of injury, MSCs produce factors that inhibit scarring and apoptosis, promote angiogenesis and stimulate host progenitors to divide and differentiate in order to repair the injured tissue. In this regard, the trophic effects of MSCs may have important clinical use.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…A suitable contrast agent for labeling rat or human MSCs, embryonic stem cells and olfactory ensheathing cells is a commercially available contrast agent based on dextran-coated SPIO nanoparticles, Endorem s (Guerbet, France). 22,33,34 Endorem can be easily incorporated by endocytosis, and its uptake does not need to be facilitated by a transfection agent, which can damage large numbers of cells. 35 On the day that nanoparticles were withdrawn, the efficiency of both rat or human MSC labeling (i.e., how many cells out of the total number of analyzed cells were labeled) was 50-70%.…”
Section: Cell Labelingmentioning
confidence: 99%
See 2 more Smart Citations
“…The implantation of this bridging hydrogel alone may not have an effect on behavioral improvement in association with scaffold implantation such as has been found in association with stem cells or neurotrophic factors implantation 23,[30][31][32] . Furthermore, a comparative study of four methacrylate hydrogels indicated that the HEMA-MOETACl hydrogel was the best carrier of mesenchymal stem cells (MSCs) in vitro and in vivo 29 .…”
Section: Discussionmentioning
confidence: 87%